Interface friction regulation method based on electro-responsive hydrogel and application thereof
Patent Information
- Application Number
- CN202610810575.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-05
- Publication Date
- 2026-09-01
AI Technical Summary
可控粘附与脱附单网络水凝胶的不足之处包括:第一,环境适应性较差
1.本发明采用水凝胶电控摩擦切换定姿单元,可在同一湿滑不规则接触界面上实现超滑运动与高阻定姿的切换。本发明设计了基于电控摩擦切换的水下定姿单元,将电响应界面摩擦调控机制与水下设备的移动、定姿需求相结合,实现水下设备在复杂湿滑环境下的顺滑运动与稳定驻留。
Smart Images

Figure CN122672601A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of mechanical friction technology, and specifically to a method for controlling interfacial friction based on electroresponsive hydrogels and its applications. Background Technology
[0002] When underwater robots and detectors conduct underwater exploration, sampling, and positioning operations, they face extremely high requirements for smooth movement, parking stability, attitude controllability, and resistance to water flow disturbances. Especially during the collection of sediment, biological, and water samples, the robot's own slippage or swaying can introduce additional water flow disturbances, disrupting the in-situ environment and directly leading to decreased sampling accuracy, sample distortion, or even sampling failure. Therefore, achieving rapid and reliable motion and attitude locking switching under complex water flow impacts, while avoiding excessive disturbances caused by mechanical movements, is crucial for ensuring high-precision underwater sampling operations.
[0003] Currently, the motion contact interfaces of underwater robots or probes are mostly made of rigid materials. Rigid materials have poor adhesion to irregular surfaces, making it difficult to form stable and effective frictional contact. In wet and slippery underwater environments, these interfaces are prone to uncontrollable movement, which not only affects operational safety but also generates significant water flow disturbances during sampling, severely limiting sampling accuracy and the reliability of detection data.
[0004] To overcome the inherent limitations of rigid materials, researchers have begun to focus on the application potential of flexible interface materials in underwater equipment. Among them, hydrogel materials are considered an ideal choice for constructing novel underwater contact interfaces due to their excellent flexibility, wet interface adaptability, and tunable physicochemical properties. However, traditional hydrogels mostly focus on passive lubrication or single-function design, making it difficult to meet the actual needs of underwater equipment for dynamic switching of interface friction states.
[0005] In existing technologies, the closest approach to this solution in the research on friction and lubrication technology for underwater equipment is the research on flexible intelligent interfaces, including controllable adhesion and desorption materials and stimulus-responsive friction and lubrication hydrogel materials.
[0006] However, existing technologies still have the following shortcomings: The limitations of controllable adhesion and desorption single-network hydrogels include: First, poor environmental adaptability. Existing research mainly focuses on controllable adhesion performance in pure water environments, with relatively weak research on adaptability to complex environmental systems (such as physiological environments and seawater environments). In practical applications, especially in underwater exploration, marine engineering, and biomedical scenarios, hydrogel materials need to cope with complex conditions such as high salinity, high humidity, dynamic fluids, and biological media. The adhesion stability, controllable response, and long-term reliability of existing materials in these environments are difficult to guarantee effectively. Second, it is difficult to synergistically optimize mechanical properties and adhesion properties. While pursuing strong adhesion and rapid desorption performance, existing hydrogel materials suffer from low mechanical properties and insufficient fatigue resistance, failing to provide stable and continuous mechanical support for the adhered object, which seriously restricts their application reliability in long-term service scenarios.
[0007] Existing stimulus-responsive hydrogels still suffer from the following technical limitations in tribological applications: First, limited response control range. The friction coefficient adjustment range of stimulus-responsive hydrogels is relatively small, making it difficult to meet the application requirements of wide-range friction control. Furthermore, pH-responsive systems have limited control windows in seawater and specific engineering environments, and ion-responsive systems are highly sensitive to ion concentration, making it difficult to guarantee response stability in complex environments. Second, potential biosafety risks. During application, temperature-responsive and light-responsive hydrogels may cause potential damage to biological tissues or the surrounding environment due to stimuli (such as temperature changes or ultraviolet light irradiation), limiting the widespread application of these materials in sensitive fields such as biomedicine. Third, insufficient environmental adaptability. Existing research is mostly focused on ideal laboratory conditions, lacking application verification under real underwater working conditions. In particular, the application of electric field-responsive hydrogels in complex environments with high ionic strength, such as salt solutions, has not been fully verified. Fourth, insufficient self-lubricating properties of hydrogels. The lubricating properties of existing single-network hydrogels are significantly limited. The friction coefficient of conventional single-network hydrogels at wet and slippery interfaces can typically only be reduced to around 0.09. For the hydrogel electro-friction attitude-fixing unit involved, if this type of material is used, its friction coefficient of 0.09 is still too high, which makes it impossible for the attitude-fixing unit to obtain the ideal extremely low motion resistance in the "super-slippery motion mode", thus generating unnecessary energy consumption and making it difficult to meet the needs of precise and energy-saving motion control.
[0008] In summary, the core technical challenge is to provide an intelligent friction control interface that combines adaptive flexible contact, a wide-range actively adjustable coefficient of friction, low friction coefficient, rapid response, no chemical residue, and good stability in real underwater environments. This interface is crucial for meeting the anti-slip braking and smooth movement requirements of underwater equipment in complex environments. Therefore, there is an urgent need to develop an interface solution capable of friction control in complex underwater environments to meet the demands of smooth movement and stable attitude maintenance in actual underwater equipment operating conditions. Summary of the Invention
[0009] To address the shortcomings of existing technologies, the present invention aims to provide an underwater motion / attitude fixation unit for an electrically controlled friction module. By deploying an electrically responsive friction unit and combining it with the logic of actual scene conditions and electric field control, it achieves low-resistance movement in the absence of an electric field and rapidly increases interface friction when an electric field is applied. It achieves stable dwelling and precise attitude fixation under combined conditions of water flow impact and variable load, thus solving the problem of device interface slippage and instability in underwater wet and slippery environments.
[0010] The first aspect of this invention provides a method for controlling interfacial friction based on electroresponsive hydrogels, comprising the following steps: A friction pair consisting of a dual-network hydrogel and an underwater device interface is provided, and the dual-network hydrogel is placed in a lubricating medium environment; The dual-network hydrogel is fixed to the working surface of the underwater device, and a working electrode is set at the bottom of the dual-network hydrogel, and a counter electrode is set on the grinding side of the hydrogel to form an electrochemical friction test circuit. A power source is provided, electrically connected to the working electrode and the counter electrode, for applying voltage to the dual-network hydrogel; By controlling the polarity of the voltage applied between the working electrode and the counter electrode, the coefficient of friction between the hydrogel surface and the interface of the underwater device can be reversibly switched.
[0011] When no voltage is applied, the surface of the hydrogel exhibits a low-friction state with a friction coefficient of approximately 0.011-0.046, enabling smooth and low-energy movement of the underwater equipment's motion interface. When different polarity voltages are applied, the surface of the hydrogel exhibits a high friction state, with a friction coefficient of approximately 0.08-0.35, achieving posture locking and anti-slip anchoring.
[0012] In some implementations, when a negative voltage is applied, the dual-network electroresponsive hydrogel exhibits a high-friction state with a friction coefficient of approximately 0.1-0.35, making it suitable for stable anchoring under heavy loads and water flow impact conditions. When a positive voltage is applied, the dual-network electroresponsive hydrogel exhibits a medium friction state with a friction coefficient of approximately 0.08-0.2, making it suitable for attitude stabilization under light load conditions.
[0013] In some embodiments, the dual-network hydrogel is prepared by ultraviolet photochemical crosslinking, and the raw materials include: Polymer monomers: 1 mol / L 2-acrylamido-2-methylpropanesulfonic acid, 2 mol / L acrylamide Crosslinking agent: 8 mol% N,N'-methylenebisacrylamide Initiator: 0.1 mol% 2-oxoglutaric acid Solvent: Deionized water.
[0014] In some embodiments, the lubricating medium environment includes, but is not limited to, deionized water, physiological saline, 0.15 mol / L La(NO3)3 aqueous solution, hyaluronic acid suspension, and phospholipid suspension.
[0015] In some implementations, the polarity voltage is a negative voltage and a positive voltage, and applying different polarity voltages means applying a negative voltage of -5V and applying a positive voltage of +5V.
[0016] In some embodiments, the power supply is an N2600 series high-precision digital source meter, operating in the first and third quadrants, serving as a source to output power to the object under test, and measuring the instantaneous current and voltage values flowing through the hydrogel and friction pair in real time; a four-wire connection is used to form the current loop and the measurement loop respectively, with the positive output terminal (IN / OUT HI) connected to the working electrode and the negative output terminal (IN / OUT / LO) connected to the counter electrode; the positive induction (SENSE HI) is connected to the working electrode and the negative induction (SENSE LO) is connected to the counter electrode.
[0017] In some embodiments, the working electrode is a platinum electrode or a copper electrode, and the counter electrode is an aluminum foil or an aluminum ball holder.
[0018] In some embodiments, the underwater equipment includes underwater robots, unmanned submersibles, autonomous underwater vehicles, underwater robotic arms, underwater core samplers, marine monitoring equipment, underwater biomimetic software equipment, underwater measurement and sensing equipment, underwater communication equipment, deep-sea mining vehicles, ship structure cleaning equipment, underwater cutting machines, in-situ antifouling testing platforms, etc.
[0019] In some embodiments, the friction control method is adapted to the following operating conditions: no load / no water flow; light load / no water flow; heavy load / no water flow; no load / water flow impact; light load / water flow impact; heavy load water flow impact.
[0020] In some implementations, the coefficient of friction is obtained by performing reciprocating friction tests using a friction and wear testing machine, with a test speed range of 0.1 mm / s to 60 mm / s.
[0021] The second aspect of this invention provides the application of the above-mentioned interfacial friction control method based on electroresponsive hydrogels in the attitude control of underwater equipment.
[0022] Compared with the prior art, the present invention has achieved the following beneficial technical effects: 1. This invention employs a hydrogel-based electro-friction switching attitude-fixing unit, enabling the switching between super-slippery motion and high-resistance attitude fixation on the same slippery, irregular contact interface. This invention designs an underwater attitude-fixing unit based on electro-friction switching, combining an electro-responsive interface friction control mechanism with the movement and attitude-fixing requirements of underwater equipment, thereby achieving smooth movement and stable abode of underwater equipment in complex, slippery environments.
[0023] 2. This invention constructs a complete underwater operation process from movement to attitude locking, and completes application verification in a simulated real detection environment. By establishing a progressive working condition verification of "light load without water flow - heavy load without water flow - light load with water flow - heavy load with water flow", it can comprehensively and realistically reflect the attitude fixing effect of the system in actual underwater operations.
[0024] 3. This invention experimentally verifies the matching law between electric field polarity and load conditions, forming a differentiated application strategy for electric field polarity. The optimal electric field mode can be selected according to different load conditions, improving the adaptability and reliability of the attitude determination system and enhancing the system's adaptability to complex underwater environments.
[0025] 4. This invention significantly reduces energy consumption and drive load in underwater or slippery environments. In the absence of an electric field, the hydrogel interface can achieve a friction coefficient as low as 0.011, significantly reducing the sliding resistance of the attitude-fixing unit during movement, reducing the power requirements and energy consumption of the drive motor, and is particularly suitable for battery-powered underwater autonomous operating equipment, extending the single-operation time.
[0026] 5. This invention improves the attitude maintenance capability under irregular contact interfaces. Under the action of a negative electric field, the coefficient of friction can reach 0.35, providing sufficient and controllable friction even on curved, rough, or slippery irregular interfaces. This effectively prevents the equipment from slipping or drifting due to water flow disturbances or gravitational torque, thus enhancing positioning reliability.
[0027] 6. This invention reduces reliance on traditional mechanical clamping or locking mechanisms. Traditional posture control on slippery interfaces often requires mechanical grippers, brake pads, or locking pins, which are prone to problems such as mud and sand jamming, seal failure, or wear in complex underwater environments. By directly controlling interface friction through an electric field, motion / posture switching is achieved without mechanical contact, improving the system's reliability in muddy and sandy underwater environments and reducing maintenance frequency and failure rate.
[0028] 7. This invention can utilize the frictional hysteresis characteristic to achieve sensorless contact state sensing. Since there are three significantly different friction coefficients (0.011 / 0.2 / 0.35) corresponding to no electric field, positive electric field, and negative electric field, the actual friction state of the interface can be inferred by monitoring the minute changes in the driving current. Thus, the adhesion state of the mechanical contact surface can be judged without adding an additional force sensor, reducing the system hardware cost.
[0029] 8. This invention can extend the service life of the mechanical interface in a grinding process. As a soft elastomer material, hydrogel itself has a friction-reducing and buffering effect on the mechanical interface; moreover, the change in the friction coefficient during electric field switching is mainly regulated by the hydrogel surface, rather than depending on changes in the mechanical interface. Under conventional ultra-low friction (0.011) mode, the rate of scratching and damage to the mechanical interface can be significantly reduced, thereby extending the service life of the entire device. Attached Figure Description
[0030] To more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0031] Figure 1 This is a schematic diagram of the application verification design of the underwater device motion interface of the present invention. In the diagram, (a) shows the hydrogel maintaining super-slippery motion under various working conditions with no electric field; (b) shows the hydrogel maintaining a stable posture under various working conditions with a negative electric field; and (c) shows the hydrogel maintaining a light-load posture under various working conditions with a positive electric field.
[0032] Figure 2 This is a schematic diagram illustrating the working principle of the electroresponsive hydrogel of the present invention.
[0033] Figure 3 These are the verification results of the matching law between electric field polarity and working conditions during the experiment using the dual-network hydrogel of this invention. Figure a shows the smooth motion state with the verification angle and no electric field; Figure b shows the fixed posture state with positive / negative electric fields; Figure c shows the fixed posture state with positive / negative electric fields and water flow impact; Figure d shows the fixed posture state with positive / negative electric fields and a light load of 20g; Figure e shows the fixed posture state with positive / negative electric fields, water flow impact, and a light load of 20g; Figure f shows the fixed posture state with a negative electric field and a heavy load of 50g, and the motion state with a positive electric field and a heavy load of 50g; Figure g shows the fixed posture state with a negative electric field, water flow impact, and a heavy load of 50g, and the motion state with a positive electric field, water flow impact, and a heavy load of 50g.
[0034] Figure 4 This is a comparison chart of the friction coefficients of the single-network / double-network hydrogels of this invention.
[0035] Figure 5 This is a graph showing the average decrease in the friction coefficient of the dual-network hydrogel of this invention compared to the single-network hydrogel.
[0036] Figure 6 This is a diagram showing the adjustment range of the interfacial friction coefficient of the dual-network hydrogel of the present invention in different lubricating media.
[0037] Figure 7This is a sensitivity comparison chart of the dual-network hydrogel of the present invention compared to the single-network hydrogel.
[0038] Figure 8 This is a diagram showing the absolute modulation range of the hydrogel interface friction coefficient of the present invention.
[0039] Figure 9 This is a real-time current graph of the hydrogel measured under the positive voltage of this invention.
[0040] Figure 10 This is a real-time current graph of the hydrogel measured under negative voltage according to the present invention. Detailed Implementation
[0041] It should be noted that the raw materials used in this invention are all commercially available products, and their sources are not specifically limited.
[0042] The working principle of the electroresponsive hydrogel of this invention is as follows: Figure 2 As shown: By adjusting the polarity of the electric field, the interaction between the polymer chains and water molecules inside the hydrogel and the diffusion dynamics of the lubricating medium are the core driving forces, which in turn affect the structure of the interfacial hydration layer, the mechanical properties of the network, etc., and ultimately achieve controllable adjustment of the friction coefficient.
[0043] Under no voltage, the attraction between polymer chains and water molecules is moderate, the network structure is uniform, the hydration layer thickness is moderate, the water molecule diffusion coefficient is maximum, and the self-healing efficiency of the lubrication layer is highest. The thinnest hydration layer achieves the lowest friction and the smallest coefficient of friction. At this point, the hydrogel interface is in a super-slippery state (coefficient of friction less than 0.01), and the hydrogel and metal interface can slide relative to each other while minimizing frictional loss.
[0044] Under negative voltage, the polymer chains have the weakest attraction to water molecules, resulting in a denser network, a thinner hydration layer, decreased lubrication, the lowest water molecule diffusion coefficient, insufficient lubrication layer replenishment, and the highest coefficient of friction. This high coefficient of friction provides the hydrogel with a significant anchoring force at the metal interface, allowing it to remain stably anchored without displacement even under heavy loads and water flow impacts.
[0045] Under a positive voltage, the polymer chains exert the strongest attraction on water molecules, inducing network swelling and increasing structural inhomogeneity. At this point, a thicker hydrated layer forms at the interface, but gel stiffness decreases, energy dissipation increases, the water molecule diffusion coefficient is moderate, viscous shear resistance dominates, and the friction coefficient is at a medium level. A moderate friction coefficient cannot withstand heavy loads, leading to anchoring failure under heavy loads, resulting in the hydrogel sliding down the plate.
[0046] When underwater equipment is moving, the hydrogel interface and the metal interface can achieve relative movement with virtually no friction loss; when underwater equipment is stationary, the hydrogel interface can achieve stable anchoring and posture fixation, and the underwater equipment can remain stationary, ensuring reliable posture fixation even under continuous waterway disturbance and external loads.
[0047] Example 1: Preparation of dual-network electroresponsive hydrogels Raw material preparation for dual-network hydrogels: First, 1 mol / L AMPS monomer, 8 mol% crosslinking agent MBAA, and 0.1 mol% photoinitiator 2-oxoglutaric acid were dissolved in 100 ml of deionized water to prepare a first network prepolymer solution. This solution was poured into a mold and polymerized under UV irradiation for 5 hours to form a first network gel. Subsequently, the gel was demolded and immersed in a second network prepolymer solution prepared with 2 M acrylamide monomer, 0.1 mol% MBAA, 0.1 mol% initiator, and 200 ml of deionized water to swell for 1 day. It was then polymerized again under UV irradiation for 1.5 hours to form a double network structure. The resulting hydrogel was then purified by immersing it in 500 ml of deionized water for one week to obtain the double network hydrogel.
[0048] Environmental media: Choose one of the following salt solutions: physiological saline, 0.15 mol / L lanthanum nitrate aqueous solution, or 0.15 mol / L aluminum nitrate aqueous solution.
[0049] Example 2: Preparation of single-network electroresponsive hydrogels Preparation of raw materials for single-network hydrogels: 5g of acrylamide monomer, 0.01g of N,N'-methylenebisacrylamide, and 0.05g of photoinitiator I2959 were dissolved in 20ml of deionized water and stirred for 15min until completely dissolved to obtain a homogeneous prepolymerized mixture. This prepolymerized solution was poured into a transparent mold, sealed, and placed under a UV light source for photocrosslinking. The UV light wavelength was 365 nm, and the light intensity was 200 mW·cm. - ², irradiation lasted for 1.5 hours. After photopolymerization, the target mono-network hydrogel was obtained.
[0050] Environmental media: Choose one of the following salt solutions: physiological saline, 0.15 mol / L lanthanum nitrate aqueous solution, or 0.15 mol / L aluminum nitrate aqueous solution.
[0051] Example 3: Electrically Controlled Tribological Performance Test I. The relationship between the experimental setup and its location is as follows: Figure 1 As shown: Slippery irregular surfaces in the motion / attitude interface of the simulation device: aluminum foil laminated on a 30mm×25mm acrylic sheet. Working condition design: 20g and 50g weights are used to simulate light load and heavy load conditions respectively; continuous water flushing for bottle washing is used to simulate environmental water flow impact and disturbance. Any combination of different working conditions is allowed Friction regulation surface in the motion / pose-setting interface of simulation equipment: hydrogel cylindrical block, with a diameter of 24mm and a height of about 10mm II. Circuit device: Power supply: N2600 series high-precision digital source meter, which operates in the first and third quadrants. It acts as a source to output power to the measured object, and measures the instantaneous current value and instantaneous voltage value flowing through the hydrogel and the friction pair in real time. For soft and wet materials such as hydrogels, a 4-wire connection measurement method is adopted, the source meter is set to voltage source mode, the output voltage is 5V, and the current limit is 0.01A. The output voltage range is 1–36V, and the current range is 0.001–0.1A.
[0052] Data acquisition: After equipping with a NE101 communication converter, connect the computer to the communication interface of the source meter to collect real-time current and voltage, and the variation curve can be drawn on the provided standard PC control software.
[0053] Hydrogel terminal electrode / working electrode: platinum / copper electrode. On the friction and wear tester, a platinum electrode is used to closely adhere to the hydrogel; in the application design experiment, a copper wire electrode is used, which is easy to move.
[0054] Counter electrode: aluminum foil plate, aluminum ball holder of the multi-functional friction and wear tester.
[0055] Wire connection in the circuit: 4-wire connection method is adopted. Special shielded test wires matching the N2600 are used. The positive output terminal (IN / OUT HI) is connected to the working electrode; the negative output terminal (IN / OUT LO) is connected to the counter electrode. The positive sense terminal (SENSE HI) is connected to the working electrode; the negative sense terminal (SENSE LO) is connected to the counter electrode. The output wires form a current loop: source meter → hydrogel → friction pair → source meter; the sense wires form a measurement loop: source meter → contact interface between hydrogel and friction pair → source meter.
[0056] The source meter outputs the set voltage of 5V through the output wires. Through the connection of the sense wires, the error caused by wire resistance is eliminated as much as possible, so that the actual voltage and actual current at the hydrogel interface can be measured relatively accurately. The real-time friction coefficient of the hydrogel interface can be measured synchronously on the friction and wear tester. The collected actual voltage and actual current are used for subsequent analysis on how the friction coefficient of the hydrogel interface is affected by electronically controlled lubrication. ( Figure 9-10 ) III. Friction and wear experiment method, for accurate measurement of friction coefficient: Sample mounting and electrode arrangement: The prepared hydrogel sample was fixed in a petri dish using underwater adhesive. A platinum (Pt) electrode was placed tightly against the bottom of the hydrogel sample as the working electrode. The entire mounted sample was then placed on the testing platform of a tribological testing machine.
[0057] The grinding system and counter electrode setup: A 6.35 mm diameter grinding ball (made of sapphire and silicon nitride) was selected and loaded onto the hydrogel surface through a ball holder, with a load set at 0.5 N. The counter electrode was placed on the ball holder and connected to a container containing lubricating medium to form a complete electrochemical tribology test circuit.
[0058] Lubricating medium and electric field application: Tests were conducted in various lubricating media, including but not limited to deionized water, physiological saline (0.9 wt% NaCl), 0.15 mol / L La(NO3)3 (lanthanum nitrate aqueous solution), hyaluronic acid suspension, and phospholipid suspension. A voltage of +5 V or -5 V was applied to the hydrogel through the bottom working electrode via a power supply, and the counter electrode was connected to the lubricating medium to form a closed circuit.
[0059] Friction Testing and Data Analysis: Reciprocating friction tests were conducted within a speed range of 0.1 mm / s to 60 mm / s. Each experiment included comparative tests under both no-electric-field and applied-electric-field conditions. The changes in the friction coefficient with time, velocity, and voltage were recorded, and the effect of the electric field on the hydrogel was analyzed. The frictional behavior of the lubricating medium interface and the regulation of the lubrication state.
[0060] Characterization of the electroresponsive mechanism: The macroscopic tribological behavior of electroresponsive hydrogels is the result of the synergistic effect of intermolecular interactions, hydration layer structure, water molecule dynamics, and network microstructure. Figure 2Molecular dynamics simulations show that the attraction of polymer chains (especially AMPS chains) to water molecules varies significantly under different electric field polarities. The attraction is strongest under a positive electric field (-5.69 kcal / (mol·Å)), intermediate under no electric field (-3.97 kcal / (mol·Å)), and weakest under a negative electric field (-2.67 kcal / (mol·Å)). This variation determines the binding state and mobility of water molecules at the interface. Under a positive electric field, the polymer chains have the strongest attraction to water molecules, leading to network swelling and increased structural inhomogeneity. The average pore size of the hydrogel network is approximately 66 μm, forming a relatively thick hydrated layer (3.668 Å), but with decreased stiffness and increased energy dissipation. Under a negative electric field, the attraction is weakest, the network shrinks and becomes denser, the average pore size of the hydrogel network is approximately 40 μm, the hydrated layer becomes thinner (2.670 Å), and the lubrication performance decreases. In the absence of an electric field, the attractive force is moderate, the network structure is uniform, and the average pore size of the hydrogel network is approximately 59 μm, providing an ideal structural basis for low friction. The water molecule diffusion coefficient further modulates the self-healing efficiency of the lubricating layer, reaching its maximum of approximately 8.49 × 10⁻⁶ in the absence of an electric field. -5 cm 2 / s, at which point the self-healing ability is strongest, achieving the lowest friction with the thinnest hydration layer. Under a positive electric field, the diffusion coefficient is moderate, approximately 7.98 × 10⁻⁶. -5 cm 2 / s, viscous shear resistance dominates, with a moderate friction coefficient. The diffusion coefficient is smallest under a negative electric field, approximately 7.60 × 10⁻⁶. -5 cm 2 At a speed of / s, insufficient lubrication layer replenishment leads to the highest friction coefficient. Therefore, the friction coefficient increases sequentially under positive electric field, no electric field, and negative electric field conditions, reflecting the synergistic competition mechanism between the hydration layer structure, network mechanical properties, and diffusion dynamics. By comparing the changes in friction coefficient under different voltage polarities and different lubricating media, combined with hydrogel swelling state, surface morphology, and interface analysis, the influence mechanism of the electric field on frictional behavior is elucidated.
[0061] Friction and wear tests were conducted using a tribological system. The hydrogel sample was fixed on a DC-powered electrode substrate to ensure uniform contact. The friction coefficients of the hydrogel interface under different polarity electric fields were obtained.
[0062] The diffusion coefficient of water molecules and the thickness of the hydrodynamic layer were determined using molecular dynamics simulation software. Infrared spectra with and without an applied electric field were recorded. The microstructure of the hydrogel before and after the application of the electric field was observed using scanning electron microscopy. The surface morphology of the hydrogel was characterized using a three-dimensional confocal white light interferometer for quantitative morphological analysis. A universal testing machine equipped with a 100 N load sensor was used to perform compression tests on the hydrogel samples at a speed of 50 mm / min. The effects of electric field polarity on the diffusion coefficient, hydrodynamic layer thickness, mechanical strength, thermal stability, and interfacial surface morphology were obtained.
[0063] Utilize Figure 1 The simulated application test shown depicts the hydrogel fixed at the moving interface of an underwater mechanical device, with the device interface serving as the friction pair. Simulations were conducted under conditions of no electric field, positive electric field, and negative electric field. Under the condition of no electric field, the coefficient of friction between the hydrogel and the mechanical interface was as low as approximately 0.011. Simulation tests were performed under water flow impact, light load, and heavy load conditions. Even under continuous water flow impact, the hydrogel maintained smooth movement without any motion stagnation due to sudden force increases; the movement was stable and without stick-slip. In this mode, the hydrogel utilizes its ultra-low friction characteristics to achieve super-slip movement with the mechanical interface, significantly reducing motion energy consumption. Simultaneously, the flexibility of the hydrogel material can adapt to the minute irregularities of the mechanical surface, buffering contact stress, thereby effectively protecting the mechanical interface, reducing surface wear, and extending the equipment's service life. Figure 1 a).
[0064] When a positive electric field is applied, the coefficient of friction at the hydrogel interface is approximately 0.2 ( ). Figure 1 c); When a negative electric field is applied, the coefficient of friction further increases to approximately 0.35 ( Figure 1 (b) Under random water flow disturbance, the hydrogel maintains stable anchorage at the interface with the mechanical equipment under the action of an electric field, without slippage or attitude swaying, effectively suppressing displacement caused by external forces. In this mode, the hydrogel induces an increase in the interface friction coefficient through the electric field, forming a high-resistance anchorage between the equipment and the mechanical interface, achieving reliable attitude fixation without slippage or swaying, which is particularly suitable for underwater precision operations, positioning, and attitude maintenance scenarios. The application potential of the friction coefficient switching by electric field polarity is verified, visually reflecting the effect of friction coefficient switching. Similar schemes include gel sliding distance, inclined plane angle, and pendulum oscillation number.
[0065] Example 4: Underwater Application Verification Experiment The hydrogel electro-controlled friction switching attitude-fixing unit of the present invention operates on the principle of controlling the direction of the electric field applied to the hydrogel material to achieve active and reversible switching of the friction state between the hydrogel material and the aluminum foil being ground on the same slippery and irregular contact interface.
[0066] Superlubricating motion (no electric field state): When no electric field is applied, the hydrogel interface is in a field-free state. In this state, the coefficient of friction between the hydrogel and the aluminum foil interface can be as low as approximately 0.011. In verification experiments, the hydrogel consistently achieved superlubricating motion regardless of whether it was subjected to water flow impact or light to heavy loads. Water flow impact did not cause significant fluctuations in friction; even with increased load, the coefficient of friction remained at an ultra-low level of around 0.011. During this process, the hydrogel and mechanical equipment interface generated a sustainable superlubricating relative motion. Figure 4 , Figure 5 Due to its extremely low frictional resistance, the energy consumption required to drive mechanical equipment is significantly reduced. Simultaneously, the inherent flexibility of hydrogel materials allows them to conform to the microstructure of irregular interfaces, buffering contact stress and thus significantly protecting the mechanical interface, reducing surface wear, and extending equipment lifespan. This mode corresponds to... Figure 1 a and Figure 3 The state shown in diagram a is suitable for scenarios requiring low resistance and high-frequency movement.
[0067] High-resistance attitude control (applied positive / negative electric field state): When it is necessary to fix mechanical equipment in a certain posture or position, an electric field of a specific direction is applied to the hydrogel through the control system. Applying a positive electric field changes the surface friction state of the hydrogel, increasing the interfacial friction coefficient to approximately 0.2. The interfacial friction force is significantly enhanced, beginning to limit the relative sliding tendency between the equipment and the aluminum plate. Applying a negative electric field results in an even higher frictional response at the hydrogel interface, with the friction coefficient further increasing to approximately 0.35. At this point, the interface can provide a strong frictional locking force. Under simulated underwater disturbance conditions, once a positive or negative electric field is applied, the hydrogel immediately forms a high-friction anchor with the mechanical equipment interface. This anchoring effect effectively resists external disturbance forces, ensuring that the equipment interfaces do not slip or wobble, achieving reliable posture locking. This process corresponds to... Figure 1 b (positive electric field) Figure 1 c (negative electric field) and Figure 3 b, c, d, e, f, and g are suitable for underwater scenarios requiring precise positioning, attitude maintenance, resistance to water flow impact, or bearing operational loads.
[0068] Through the above working process, the present invention utilizes the wide range of control of the friction coefficient of the hydrogel interface by the electric field to achieve the coordinated operation of two completely different functions, "movement" and "posture fixation", on the same wet and slippery irregular contact interface.
[0069] Operating conditions: No load / no water flow; light load / no water flow; heavy load / no water flow; no load / water flow impact; light load / water flow impact; heavy load water flow impact, etc.
[0070] Smooth motion phase: With no voltage applied by the control system, the hydrogel surface exhibits low friction, achieving smooth, low-energy motion with a sliding speed of approximately 300 mm / s. Attitude locking stage: The control system applies voltages of different polarities to the electrodes, making the surface of the hydrogel exhibit a high-friction state, thereby achieving attitude locking and anti-slip anchoring. During the anchoring period, the hydrogel block was gently pushed a certain distance (applied initial velocity) and did not slide down, proving that it can be stably anchored.
[0071] Tribological testing procedure: The prepared hydrogel sample was fixed in a petri dish using underwater adhesive. A platinum (Pt) electrode was placed tightly against the bottom of the hydrogel sample as the working electrode. The entire sample was then placed on the testing platform of a tribological testing machine. A 6.35 mm diameter grinding ball (made of sapphire, silicon nitride, etc.) was selected and loaded onto the hydrogel surface through a ball holder, with a load set to 0.5 N. A counter electrode was placed on the ball holder and connected to a container containing a lubricating medium, forming a complete electrochemical tribological testing circuit. After applying voltage, the positive and negative ions inside the hydrogel migrated directionally towards the electrode with opposite polarity. As the energizing time increased, the ion migration gradually stabilized, and the overall conductivity of the material showed an increasing trend, manifested as a slow increase in current value over time. Figure 9 , 10 Tests were conducted in various lubricating media, including but not limited to deionized water, physiological saline (0.9 wt% NaCl), 0.15 mol / L La(NO3)3 (lanthanum nitrate aqueous solution), hyaluronic acid suspension, and phospholipid suspension. A +5 V or [other voltage] was applied to the hydrogel via the bottom working electrode using a power supply. A voltage of 5 V was applied, and the electrodes were connected to a lubricating medium to form a closed circuit. Reciprocating friction tests were conducted within a speed range of 0.1 mm / s to 60 mm / s. Each group of experiments included comparative tests under no electric field and with an applied electric field. Figure 6 ),from Figure 6 As can be seen, regardless of the polarity of the applied electric field, the introduction of an electric potential consistently leads to an increase in the interfacial friction coefficient. The frictional response of the dual-network hydrogel under the action of an electric field exhibits a significant medium dependence. When different solutions such as deionized water (DI), physiological saline (NaCl), lanthanum nitrate aqueous solution (La(NO3)3), hyaluronic acid (HA@PBS), phospholipids (DMPC@DI), and aluminum nitrate aqueous solution (Al(NO3)3) are used as lubricating media, the degree to which the electric field polarity modulates the friction coefficient varies. Figure 6The red line (DN@F) represents the variation of the hydrogel interfacial friction coefficient over a wide velocity range without an electric field, the blue line (DN@N) represents the variation under a negative electric field, and the green line (DN@P) represents the variation under a positive electric field. However, all systems exhibit observable changes in their tribological state due to the electric field, providing a reliable data foundation for application verification designs. Figure 7 and Figure 8 As can be seen, compared to traditional single-network hydrogels, dual-network hydrogels not only possess the same electro-responsive tribological properties, but also exhibit significantly enhanced tribological response sensitivity. This phenomenon is particularly prominent in systems using physiological saline as a lubricant, where the friction coefficient sensitivity is increased by approximately 800%. Figure 7 The scope of regulation is nearly an order of magnitude. Figure 8 Although other lubricants have not achieved such extreme modulation ranges, they still exhibit a significantly higher electric field response enhancement effect than single-network systems, fully demonstrating the universal advantage of dual-network structures in improving interfacial triboelectric modulation capabilities.
[0072] V. Application Verification Experiment: With no voltage applied, the wire electrodes are connected as described in the circuit diagram, and the power supply voltage is set to 0V. The hydrogel surface exhibits a super-slippery state. At this point, the hydrogel block is gently placed on a flat plate with a 17.5° incline. Upon release, the hydrogel block slides down the plate to the bottom at a speed of approximately 300 mm / s. Figure 3 a).
[0073] The same hydrogel was placed back at the starting point of the plate. The power supply was set to -5V, and the meter showed that current was flowing. The hydrogel was gently placed on the plate, and after releasing it, the hydrogel did not move along the plate. Even after gently pushing it with your hand, it did not slide down, indicating that the hydrogel was stably anchored to the metal interface at this time. Figure 3 b, DN@N). A simulated underwater disturbance environment was created by continuously impacting the hydrogel-metal interface with a water flow for 3 seconds or more using a wash bottle. The hydrogel block remained stationary during this time, indicating that even under the combined effects of negative voltage and continuous water flow impact, the hydrogel could still be stably anchored to the metal interface. Figure 3 c, DN@N). After the continuous water flow ceased, a 20g weight was gently pressed onto the hydrogel to simulate a light load. Upon release, the hydrogel remained stably anchored without slippage. Figure 3 d, DN@N). With a 20g weight present, the hydrogel remained stable at the contact point with the plate using a wash bottle after continuous impact. Figure 3 e, DN@N). Then the 20g weight was removed, and a 50g weight was gently pressed onto the hydrogel. After releasing the weight, there was no slippage. Figure 3f, DN@N), with a 50g weight present, the hydrogel remained stable at the contact point between the plate and the hydrogel when continuously impacted by a wash bottle. Figure 3 f, DN@N). This demonstrates that under negative voltage, the hydrogel can maintain stable anchorage with the metal interface under light / heavy loads and continuous water flow impact.
[0074] The same piece of hydrogel was placed back at the starting point of the plate. The power supply was set to +5V, and the meter showed that current was flowing. The hydrogel was gently placed on the plate, and after releasing it, the hydrogel did not move along the plate. Even after gently pushing it with my hand, it still did not slide down. Figure 3 b, DN@P), indicating that the hydrogel and metal interface are stably anchored at this point. A continuous water flow is applied to the hydrogel-metal interface for 3 seconds or more to simulate an underwater disturbance environment; the hydrogel block still does not move during this time. Figure 3 c, DN@P), indicating that the hydrogel can still be stably anchored to the metal interface under the continuous action of positive voltage and water flow impact. After the continuous water flow impact is stopped, a 20g weight is gently pressed on the hydrogel to simulate a light load. After the weight is released, the hydrogel still remains stably anchored and no slippage is observed. Figure 3 d, DN@P). With a 20g weight present, the hydrogel remained stable at the contact point with the plate using a wash bottle after continuous impact. Figure 3 e, DN@P). Then remove the 20g weight and replace it with a 50g weight, gently pressing it onto the hydrogel. After releasing the weight, the hydrogel with the 50g weight pressing down slides down the plate at a speed of approximately 100mm / s. Figure 3 f, DN@P). A 50g weight is then placed back on the hydrogel, and a water jet is used to impact the hydrogel with a wash bottle. Upon release, the hydrogel quickly slides down the plate to the bottom. Figure 3 g, DN@P). This indicates that under positive voltage, the hydrogel can achieve anchoring and orientation stabilization between the hydrogel interface and the metal interface under light load, but under heavy load, the anchoring and orientation stabilization is unstable.
[0075] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the methods and techniques disclosed above without departing from the scope of the present invention to create equivalent embodiments. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A method for controlling interfacial friction based on electroresponsive hydrogels, characterized in that, Includes the following steps: A friction pair consisting of a dual-network hydrogel and an underwater device interface is provided, and the dual-network hydrogel is placed in a lubricating medium environment; The dual-network hydrogel is fixed to the moving working surface of the underwater device, and a working electrode is set at the bottom of the dual-network hydrogel. A counter electrode is provided on the grinding side of the hydrogel to form an electrochemical friction test circuit; A power source is provided, electrically connected to the working electrode and the counter electrode, for applying voltage to the dual-network hydrogel; By controlling the polarity of the voltage applied between the working electrode and the counter electrode, the coefficient of friction between the hydrogel surface and the interface of the underwater device can be reversibly switched. When no voltage is applied, the surface of the hydrogel exhibits a low-friction state with a friction coefficient of approximately 0.011-0.046, enabling smooth and low-energy movement of the underwater equipment's motion interface. When different polarity voltages are applied, the surface of the hydrogel exhibits a high friction state with a friction coefficient of approximately 0.08-0.35, thereby achieving posture locking and anti-slip anchoring.
2. The method for controlling interfacial friction based on electroresponsive hydrogels according to claim 1, characterized in that, When a negative voltage is applied, the dual-network electroresponsive hydrogel exhibits a high-friction state with a friction coefficient of 0.1-0.35, making it suitable for stable anchoring under heavy load and water flow impact conditions. When a positive voltage is applied, the dual-network electroresponsive hydrogel exhibits a medium friction state with a friction coefficient of 0.08-0.2, making it suitable for attitude fixation under light load conditions.
3. The method for controlling interfacial friction based on electroresponsive hydrogels according to claim 1, characterized in that, The dual-network hydrogel was prepared by ultraviolet photochemical crosslinking, and the raw materials included: Polymer monomers: 1 mol / L 2-acrylamido-2-methylpropanesulfonic acid, 2 mol / L acrylamide Crosslinking agent: 8 mol% N,N'-methylenebisacrylamide Initiator: 0.1 mol% 2-oxoglutaric acid Solvent: Deionized water.
4. The method for controlling interfacial friction based on electroresponsive hydrogels according to claim 1, characterized in that, The lubricating medium environment includes, but is not limited to, deionized water, physiological saline, 0.15 mol / L La(NO3)3 aqueous solution, hyaluronic acid suspension and phospholipid suspension.
5. The method for controlling interfacial friction based on electroresponsive hydrogels according to claim 1, characterized in that, The polarity voltage refers to negative voltage and positive voltage. Applying different polarity voltages means applying a negative voltage of -5V and applying a positive voltage of +5V.
6. The method for controlling interfacial friction based on electroresponsive hydrogels according to claim 1, characterized in that, The power supply is an N2600 series high-precision digital source meter, operating in the first and third quadrants. It outputs power to the object under test as a source, and measures the instantaneous current and voltage values flowing through the hydrogel and friction pair in real time. A four-wire connection is used to form the current loop and the measurement loop respectively. The positive output terminal (IN / OUT HI) is connected to the working electrode, and the negative output terminal (IN / OUT / LO) is connected to the counter electrode. The positive induction (SENSE HI) is connected to the working electrode, and the negative induction (SENSE LO) is connected to the counter electrode.
7. The method for controlling interfacial friction based on electroresponsive hydrogels according to claim 1, characterized in that, The working electrode is a platinum electrode or a copper electrode, and the counter electrode is an aluminum foil or an aluminum ball holder; The underwater equipment includes underwater robots, unmanned submarines, underwater autonomous vehicles, underwater robotic arms, underwater core samplers, marine monitoring equipment, underwater biomimetic software equipment, underwater measurement and sensing equipment, underwater communication equipment, deep-sea mining vehicles, ship structure cleaning equipment, underwater cutting machines, and in-situ antifouling testing platforms.
8. The method for controlling interfacial friction based on electroresponsive hydrogels according to claim 1, characterized in that, The friction control method is suitable for the following working conditions: no load / no water flow; light load / no water flow; heavy load / no water flow; no load / water flow impact; light load / water flow impact; heavy load water flow impact.
9. The method for controlling interfacial friction based on electroresponsive hydrogels according to claim 1, characterized in that, The coefficient of friction was obtained by reciprocating friction test using a friction and wear testing machine, with a test speed range of 0.1 mm / s to 60 mm / s.
10. The application of the method according to any one of claims 1 to 9 in attitude control of underwater equipment.